Proximate composition and anti-nutritional factors in Mucuna pruriens (velvet bean) seed flour as affected by several processing methods - Clement Chinedum Ezegbe; Justina Nne Nwosu; Clifford Ifeanyi Owuamanam; Tope Adeyemisi Victor-Aduloju; Smith G. Nkhata (Heliyon, 2023)
Mucuna pruriens seed being an underutilized legume with antinutrients was processed to reduce antinutrients and improve nutritional quality. The seeds were cleaned, washed and subjected to single treatments of soaking (24 h, 48 h, 72 h), cooking (20 min, 40 min, 60 min, 80 min), roasting (10 min, 15 min, 20 min), germination (24 h, 48 h, 72 h) and fermentation (24 h, 48 h, 72 h). Combined treatments: soaking (72 h) + cooking (60 min); germination (48 h) + roasting (15 min); germination (48 h) + cooking (60 min); fermentation (72 h) + roasting (15 min) were also separately carried out. Proximate composition and antinutrients were evaluated. Crude protein ranged from 25.34 to 29.50%, ash 3.02–3.82% and crude fibre 0.70–4.69. Crude protein was increased by single and double treatments while ash content was increased by only single treatments. All the treatments reduced the crude fibre. For single and double treatments, phenol, L-3,4-dihydroxyphenylalanine and trypsin inhibitor were in the range of 0.69–3.49%, 0.01–6.83% and 0.00–12.58 TIU/mg protein respectively. This research indicated that the use of up to 72 h soaking, 80 min cooking, 20 min roasting, 72 h germination or 72 h fermentation (Rhizopus oligosporus) is not adequate to reduce phenol and L-3,4-dihydroxyphenylalanine in Mucuna pruriens seed flour to below the recommended safe limits of 0.003% and 0.1% respectively. The double treatment of 72 h fermentation +15 m roasting was the only treatment that reduced L-3,4-dihydroxyphenylalanine to safe limit of 0.01%.